Awareness of Hepatitis B Vaccination in Rural Area: A Survey (Journal of Current and Advance Medical Research, 2014)
Background: The awareness regarding Hepatitis B vaccination is necessary in the general population of Bangladesh.Objective: This study was carried out to determine the level of knowledge and the vaccination coverage of hepatitis B virus in rural population.Methodology: This cross sectional study was conducted at Bangladesh Institute of Administration and Management (BIAM), Dhaka, Bangladesh from February 2011 to April 2011. Sirajdikhan upazila of Munshiganj District was taken as a study place. All the villagers with an age group of 15 to 55 years were taken as study population. Result: A total number of 30 respondents were recruited of which male (60.0%) is predominant than female (40.0%). The mean age with SD was 23±7.256 years (range 15-53 years). Majority has told about the knowledge regarding the sequel of hepatitis B virus infection (33.3%). Almost all respondents (96.7%) are unknown about the treatment of HBV infection. Majority (76.7%) are unknown regarding taking HBV vaccination. Nobody has given positive answer in response to take vaccine. Conclusion: In conclusion information and knowledge regarding HBV infection and vaccination is very poor in the rural area of Bangladesh.DOI: http://dx.doi.org/10.3329/jcamr.v1i1.19558J Curr Adv Med Res 2014;1(1):3-7